Fasilitasi Masyarakat Desa Wagir Kidul dalam Tata Cara Pemulasaran Jenazah - Putri Handayani; Fuad Fitriawan; Risa Alfiyah Ulfa (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The treatment of the corpse is one of the Islamic Shari'a guidance that has been taught by the Prophet Muhammad, but most people do it based on habit alone even though among the important issues related to human relations with other humans is the problem of caring for the corpse. This research aims to be able to increase knowledge and insight related to the procedure for the care of the corpse. This research uses the ABCD (asset based community driven development) method. The results that have been obtained are the implementation of training activities on how to care for corpses. The community has high enthusiasm enthusiasm in this activity.